Determinant of Macro-Economics: Does Income Inequality Influence Happiness? Evidence From Indonesia - Furwanti, Reni; Lestari, Dini Maulana; Muflikha, Muflikha; Wibowo, Muhammad Ghafur (JEJAK: Jurnal Ekonomi dan Kebijakan, 2021)
This research aims to see does income inequality determines the happiness of Indonesian. This is important because there is a unique condition where Indonesia to be one of the developing nations which have a complexity of the income inequality issue, but it still has a high happiness index rate. This research uses cross-sectional data consisting of multiple indicators of all the variables from 34 provinces of Indonesia such as inflation, unemployment, and government investment as the macroeconomic factors, which have a direct impact on income inequality as well as happiness index, and this research uses path analysis model.The result delineates that although macro economics variables and income inequality have negative correlation toward happiness of Indonesian, it it not fully effected on it because most happiness of Indonesians are coming from another aspect such as socio-culture and religiosity